Petrography, mineralogy and geochemistry of Baran Lak magnesite and associated rocks, Khuzdar, Balochistan, Pakistan - Bashir, Erum; Naseem, Shahid; Naseem, Sadaf; Sheikh, Shamim Ahmed; Shirin, Khaula (Journal of Himalayan Earth Sciences, 2004)
The Baran Lak massif, displays a complete ophiolitic sequence in the northern part of Bela Ophiolite. Magnesite veins are irregular and intersect each other at different angles forming netting pattern within ultramafic rocks. Geochemical, mineralogical and petrographical investigations of magnesite and associated ophiolitic rocks (Aptian- Maastachian) of Baran Lak area, Balochistan, were conducted to specify the nature of these deposits. Quantitative estimation of important major elements of magnesite has been carried out. Mutual plots between CaO, MgO, I.R. and R2O3 suggest that the magnesite is mainly derived from high Mg and low Fe bearing olivines and pyroxenes. The low contribution of alumina-silicates (feldspars) is also reflected in country rock by low R2O3. The plot of MgO vs. MgO/CaO ratio is evidenced for gradual depletion of Mg at the expense of Ca, probably due to interaction with groundwater. Chemically they are MgCO3 in which MgO ranges 42-44 % with minor amount of CaO (av. 3 %), insoluble residue, Fe and Al. X-ray studies revealed magnesite occurs as the major mineral along with chlorite as minor one. Petrographic studies of host rocks revealed partly to completely serpentinized equivalents of harzburgite, dunire, wehrlite and pyroxenite. These ultramafic rocks are highly altered into serpentine with subordinate amount of chlorite and sericite. At places small lenses of dunite and wehrlite and some basic intrusive rocks (sill/dyke) consisting of gabbro and diorite were also identified in the area.